Sustainable tourism practices through the eyes of the tourist: a case study of a tour operator - Calnaryte, Laura (2022)
This paper main aim is to find out the importance of sustainable tourism practices from a tourist point of view. The research study took place at Back-Roads Touring - a tour operator that specializes in small group touring for senior’s travellers from Australia, New Zealand, USA and Canada. The study had four objectives, however the focus was to find out which tourism practices were the most important to the respondents during a Back-Roads tour and which tourism options the respondents identify as sustainable tourism options. An online questionnaire was used to answer the objectives of the study. In total 1322 clients received an online questionnaire out of which 182 filled in the survey. The results showed that the respondents valued the most ‘small group touring’ and ‘having an experienced tour leader’. Furthermore, the respondents were not seeking for more sustainable tourism practices neither willing to donate money to local charities/non- profit organizations. This finding shows that the clients are content with a current model of a tour, are willing to return, however price and quality will play a key role in a future decision making. Moreover, one of the objectives of this study was to find out if the clients valued sustainable tourism certification. The results showed that the respondents were not aware of the sustainable tourism certification that the company obtained, however slightly over half of the respondents said that the knowledge of the certification had positively influenced them to travel again with the company.